2019
DOI: 10.1016/j.neuroscience.2018.11.040
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Intermittent Hypoxia Induces Robust Astrogliosis in an Alzheimer’s Disease-Relevant Mouse Model

Abstract: Sleep disturbances are a common early symptom of neurodegenerative diseases, including Alzheimer's disease (AD) and other age-related dementias, and emerging evidence suggests that poor sleep may be an important contributor to development of amyloid pathology. Of the causes of sleep disturbances, it is estimated that 10%-20% of adults in the United States have sleepdisordered breathing (SDB) disorder, with obstructive sleep apnea accounting for the majority of the SBD cases. The clinical and epidemiological da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 49 publications
1
12
0
Order By: Relevance
“…Astrocytes are also the main glia cells which produce and secrete hepcidin [13,30]. Studies have demonstrated that CIH exposure could further induce the activation of astrocytes in APP/PS1 mice and exacerbate the pathogenesis of disease [3]. Coincidentally, results of the present study indicated the increased astrocyte activation during CIH exposure, and the expression level of hepcidin also increased concomitantly (Figure 1).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Astrocytes are also the main glia cells which produce and secrete hepcidin [13,30]. Studies have demonstrated that CIH exposure could further induce the activation of astrocytes in APP/PS1 mice and exacerbate the pathogenesis of disease [3]. Coincidentally, results of the present study indicated the increased astrocyte activation during CIH exposure, and the expression level of hepcidin also increased concomitantly (Figure 1).…”
Section: Discussionsupporting
confidence: 76%
“…Epidemiological study has demonstrated that the number of OSA patients worldwide has exceeded 9.36 million, and it is becoming a serious global problem [2]. OSA has been identified as an early risk factor for developing neurodegenerative disease, such as Alzheimer's disease (AD) [1,3]. Clinical studies have shown that OSA could accelerate the progression of AD by increasing the formation and accumulation of Aβ 42 in the cerebrospinal fluid (CSF) [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…It is unclear why, unlike previous literature, AHI rather than oxygen desaturation was associated with cognitive deficit in our cohort, though it could be due to the different manifestations in SAS in the elderly population and in the general population (Al Lawati et al, 2009;Heinzer et al, 2015). The relationship between intermittent hypoxia and cognition remain complex, however, and animal studies have suggested that intermittent hypoxia may not directly impair brain structure (Jorba et al, 2017), but may play a role in the etiology of Alzheimer's Disease (Shiota et al, 2013;Menal et al, 2018;Macheda et al, 2019). Nevertheless, fragmented sleep and excessive daytime sleepiness have been shown to modify the relationship between AHI and several co-morbidities (Nena et al, 2012;Ren et al, 2016) and could contribute to cognitive decline in SAS patients (Zhou et al, 2016).…”
Section: Discussionmentioning
confidence: 55%
“…[93][94][95] Chronic intermittent hypoxia can induce neurodegenerative changes to brain tissue that may predispose patients to delirium. 96,97 Finally, research has shown that the presence of plasma tryptophan, 86,98 a precursor of the neurotransmitter serotonin, and inflammatory biomarkers (procalcitonin and C-reactive protein) 99-101 may be linked with the development of delirium. The mechanism behind C-reactive protein and delirium appears to be associated with a disruption in the BBB due to generation of reactive oxygen species.…”
Section: Icu Coursementioning
confidence: 99%